Hambatan Implementasi Akad Mudharabah pada PT. BPR Syariah Kotabumi Lampung Utara - Istiqomah Istiqomah (Fakultas Ekonomi Dan Bisnis Islam IAIN Metro, 2019)
Mudarabat financing is an agreement between Shahibul Mall and Mudarib to carry out business activities. In Kotabumi Syariah BPR, mudharabah financing is classified as financing with a low number of customers. The purpose of this study is to determine the obstacles in the implementation of mudharabah contract in PT BPR Syariah Kotabumi. The research method used is a field research method that is descriptive qualitative in nature. Methods of data collection are interview methods and documentation. Analysis of the data used is a qualitative data analysis technique with inductive thinking. The low mudharabah financing of PT BPR Syariah Kotabumi is caused by several inhibiting factors which come from customers such as moral hazard risk, customer transparency, type of business financed by the bank, customer productivity in managing the business, small demand for financing from customers, and factors from internal bank, namely the absence of a supervisory board that fosters and directs customers in managing the business, the low interest of the bank in channeling mudharabah financing products, lack of competent marketing human resources. Efforts made by PT BPR Syariah Kotabumi to minimize obstacles in the implementation of mudharabah financing contracts, namely customer business feasibility analysis, providing financing to customers with clear economic conditions, improving the quality of HR (Human Resources) internal BPR Syariah Kotabumi.